A Program for Parents’ Screen Time Reduction for Preschool Children: A Quasi-experimental Study - Boonmun, Wisanee; Rutja Phuphaibul; Sirichai Hongsanguansri; Apawan Nookong; Natkamol Chansatitporn (Pacific Rim International Journal of Nursing Research, 2023)
Excessive screen time affects the development and health outcomes among children. This quasi-experimental study examined the effects of the newly developed Parents’ Screen Time Reduction for Preschool Children Program, a training program for parents’ planned behaviors and the screen time reduction of their children. The participants were dyads of parents and preschool children aged 2-5 years, where the child’s screen time was more than one hour per day. Sixty-seven parents were recruited from two childcare centers in a province in northeast Thailand, comprising 35 in the experimental group and 32 in the control group. Instruments to measure study outcomes focused on parents’ attitudes, subjective norms, perceived behavioral control, and intentions, and the distal result was behaviors. For children, the outcome was screen time reduction. Data analyses were descriptive statistics, chi-square, independent t-test, Mann-Whitney U test, and generalized estimating equations. The findings revealed that the children’s screen time in the experimental group decreased significantly more at one week and two months after the completion of the intervention than that of the control group. The mean scores of parents’ attitudes and parents’ behaviors in the experimental group were significantly more positive higher than those in the control group immediately after the intervention; the mean score of parents’ perceived behavior control was significantly higher than that of the control group two months after the intervention. Nurses and teachers can use this program among parents to perform appropriate screen time behaviors to promote development and health outcomes among children. However, further testing of the program using randomized controlled trials is required before widespread use in practice.